House prices, disposable income, and permanent and temporary shocks - Fraser, Patricia; Hoesli, M.; McAlevey, L. (School of Economics and Finance, Curtin Business School, 2009)
This paper specifies a two-variable system of house prices and income for N.Z., U.K. and the U.S., covering periods from 1973:4 through 2008:2. The analysis allows the identification of differences in house price-income relationships over sub-periods and, using an SVAR approach, compares the responses of house prices when faced with permanent and transitory shocks to income. It continues by decomposing each historical house prices series into their permanent, temporary and deterministic components. Our results suggest that while real house prices have a long-run relationship with real income in all three economies, the responsiveness of house prices to innovations in income will vary over both time and markets depending on whether the income disturbances are viewed as permanent or temporary. The evidence suggests that N.Z. and U.K. housing markets are sensitive to both permanent and transitory shocks to income while the U.S. market reacts to temporary shocks with the permanent component having a largely insignificant role to play in house price composition. In N.Z. the temporary component of house prices has tended to be positive over time, pushing prices higher than they would have been otherwise while in the U.K. both permanent and temporary components have tended to reinforce each other. Overall, there is no clear consistent global pattern regarding the importance of these shocks which implies that housing markets will react differently to the vagaries of global and domestic economic activity driving such shocks.